Dental care for the visually impaired: An integrative review (Research, Society and Development, 2024)
Oral health is an important parameter for patients' quality of life and must be made available efficiently to all individuals. Visually impaired people have some limitations inherent to their condition that end up making it difficult to identify oral lesions and, therefore, dental care as well as oral hygiene guidelines must be offered in an accessible and continuous manner. In view of what was previously described, the aim of the work presented here is to demonstrate, through an integrative review, how dental care is provided for visually impaired people. To this end, a search was carried out in the Virtual Health Library (VHL) databases, which contain the following databases: PUBMED, LILACS, MEDLINE, MEDCARIB, PAHO-IRIS, WHOLIS. In this way, the descriptors “oral hygiene”, “blind people”, “dental surgeon” and “audio-tactile” were used, in English, Portuguese and Spanish in the time frame from 2019 to 2023. Despite the high importance, the This topic is still neglected both by the population, who seek dental services only in extreme cases, and by professionals who are often not qualified to care for patients with visual impairments. The use of playful-educational and audio-tactile materials are strategies that effectively help the education and oral health of individuals with visual impairments. The findings obtained in this study reinforce the need to use appropriate materials to assist in the provision of dental services for people with visual impairments.